The Neurobiological Underpinnings of Psychoanalytic Theory and Therapy - Solms, Mark Leonard (Frontiers in Behavioral Neuroscience, 2018)
This article outlines the basic scientific claims of psychoanalytic theory and therapy, and spells out their neurobiological underpinnings.